Rol de enfermería y su intervención en la prevención de diabetes en adultos de 40 - 60 años, Unidad Anidada San Vicente de Paúl, Pasaje, El Oro, octubre 2018 – abril 2019 - Pilco de la Vega, Karem Jahaira (2019)
Around the world, millions of people are at risk of acquiring Diabetes, a disease that at the moment is becoming a serious health problem, even in recent years an increase in Diabetes in children has been detected. The reason for the present investigation is to determine the mechanisms that exist to prevent this disease and an important part of the prevention is the nursing staff, with the support of the Ministry of Health, being the education of the community the ideal mechanism, to indicate the people who can be prevented or delayed with actions such as losing weight, following a healthy eating plan, performing regular physical activities, not smoking. Health is an important element for the development of countries, this is why diabetes is being controlled, and an effective mechanism to prevent this disease is diabetological education. This disease is unfortunately growing and it is the nursing staff who should be inserted in a national prevention program, one of the mechanisms being the talks with the community, for which it is necessary that it be actively involved, the community and especially its leaders have a historical responsibility to prevent the diabetes of their fellow citizens. Having determined through the study that one of the mechanisms is the use of diabetes educators, it has also been determined that messages that allow people at risk to carry out physical activities and try to combat overweight and obesity should be reinforced.